Costing healthy diets and measuring deprivation: New indicators and modeling approaches - Pauw, Karl; Ecker, Olivier; Thurlow, James; Comstock, Andrew R. (International Food Policy Research Institute, 2021)
One of the greatest global challenges today is ensuring widespread availability and equitable access to affordable, nutritious foods produced in an environmentally sustainable manner. A rich literature exists around the definition of a healthy diet and the drivers of dietary change. We contribute to this literature by proposing a new quantifiable diet deprivation measure estimated from standard household consumption and expenditure surveys. The Reference Diet Deprivation (ReDD) index measures the incidence, breadth, and depth of diet deprivation across multiple, essential food groups in a single indicator. Although useful as a standalone measure, we show how ReDD can be integrated into an economywide model to examine changes in household diet quality under different simulation scenarios. Using Nigeria as case study, hypothetical agricultural productivity growth scenarios reveal that dairy, pulses, fruit, and red meat value chains have the greatest potential to reduce overall diet deprivation in Nigeria per unit of GDP growth generated, while productivity growth in more widely consumed crops such as cereals and root crops do little to improve diet quality. These findings have implications for the prioritization of agricultural development initiatives aimed at improving the quality of diets. More generally, the integration of a diet quality indicator in an economywide model allows for a deeper understanding of the drivers of dietary change.